Direct Smartphone Disc Video Documentation for Pediatric Glaucomas During Evaluation Under Anesthesia. Issue 8 (August 2019) - Pujari, Amar; Selvan, Harathy; Goel, Siddhi; Dada, Tanuj
Abstract : The newer version of iPhone, that is iPhone Xs max camera application is opened and a video mode is selected with a with continuous light source on. This device is now slowly advanced towards the patient's eye (pharmacologically dilated while evaluating under anesthesia) and the optic disc and peripapillary area findings can be documented with great ease. This video graphic and/or standstill images obtained from the video can be stored in the smartphones or on the cloud memory for future assessment/comparison. Abstract : Supplemental Digital Content is available in the text.